1972
DOI: 10.1002/apmc.1972.050260106
|View full text |Cite
|
Sign up to set email alerts
|

Struktur und eigenschaften von ABS‐polymeren. VIII. Das elutionsverhalten von homo‐ und copolymeren aus styrol und acrylnitril in der gelchromatographie. Aufstellung einer eichkurve für lösungsmittel unterschiedlicher güte

Abstract: An einer Reihe von Polystyrol‐, Polyacrylnitril‐ und Styrol‐Acrylnitril‐Copolymerfraktionen mit 12, 25 und 52 Gew.‐% Acrylnitril wurde das Elutionsverhalten in der Gelchromatographie untersucht. Durch Auftragen des Molekulargewichts über dem Elutionsvolumen erhält man in den Lösungsmitteln Chloroform und Dimethylformamid (DMF) für jede Probenreihe eine eigene Eichbeziehung. Bei Verwendung des hydrodynamischen Volumens und der ungestörten Knäueldimensionen erhält man universelle Eichbeziehungen mit Ausnahme von… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 16 publications
1
6
0
2
Order By: Relevance
“…A similar observationwas reported on changing from chloreform to DMF (13) and from tetrahydrofUran to DMF (14). Methyl ethyl ketone and DMF (a = 0.60 -0.64) are poor solvents for polystyrene, and in GPC separations with these eluents the plot of log hydrodynamic volume versus VR for polystyrene is displaced to high VR with respect to a plot for,another polymer for wnich these same eluents are good solvents (13,15). Similar results have been reported for polystyrene at 35°C in the thetasolvent cyclohexane (15,17,18).…”
Section: Results and Disgussionsupporting
confidence: 86%
See 4 more Smart Citations
“…A similar observationwas reported on changing from chloreform to DMF (13) and from tetrahydrofUran to DMF (14). Methyl ethyl ketone and DMF (a = 0.60 -0.64) are poor solvents for polystyrene, and in GPC separations with these eluents the plot of log hydrodynamic volume versus VR for polystyrene is displaced to high VR with respect to a plot for,another polymer for wnich these same eluents are good solvents (13,15). Similar results have been reported for polystyrene at 35°C in the thetasolvent cyclohexane (15,17,18).…”
Section: Results and Disgussionsupporting
confidence: 86%
“…Fora simple pore structure, the total internal pore volume Vi is related to the surface area S by vi = y r s/2 (12) where r is the average pore size of the pore size distribution and y is a numerical factor which depends on the pore geometry and on the definition of mean pore size (28). Weshall therefore assume that S is directly proportional to V., so that in equation (11) (4), (5) and (11) suggests that KP is given by (13) where KP is the distribution coefficient for polymer-sorbent interaction and will.be · greater than unity when polymer is retarded in the stationary phase. In a somewhat simpler thermodynamic interpretation of a network-limited GPC Separation (29), it was suggested that KP is determined by an enthalpy contribution, i.e.…”
Section: Thermodyeamic Interpretationmentioning
confidence: 99%
See 3 more Smart Citations